2013
DOI: 10.5455/aim.2013.21.237-240
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Diode Laser in the Reduction of Targeted Periodontal Pathogens

Abstract: Introduction:Periodontal disease belongs to a group of diseases with more than one cause, it is a disease of a multifactorial etiology. Although bacteria are the main cause of the disease, immunoinflammatory reaction of the host is responsible for the majority of destructive changes in periodontal tissue. The main issue in the evaluation of the success of periodontal therapy is the pluralism of the bacteria and their dynamic changes during the duration, on the one hand, and the possible inaccuracy of classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…Thanks to curettage effect, the laser eliminates the sulcular epithelium infected in a total and complete way than conventional methods of treatment with manual tools (30), without any kind of damage to the underlying connective tissue and reducing the bacterial load of Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis (31), which easily penetrate within the sulcular epithelium. Furthermore there is a scientific evidence on the direct antimicrobial effect of diode laser against levels of Targeted Periodontal Pathogens (32). According to Kreisler (2005) the greatest reduction in the degree of tooth mobility and probing depth in the group of patients who underwent SRP + laser therapy can be mainly attributed not to the killing of bacteria in periodontal pockets, but rather to the complete removal of infected sulcular epithelium, which leads to greater attack of the connective tissue (33).…”
Section: Middle Value Pmentioning
confidence: 99%
“…Thanks to curettage effect, the laser eliminates the sulcular epithelium infected in a total and complete way than conventional methods of treatment with manual tools (30), without any kind of damage to the underlying connective tissue and reducing the bacterial load of Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis (31), which easily penetrate within the sulcular epithelium. Furthermore there is a scientific evidence on the direct antimicrobial effect of diode laser against levels of Targeted Periodontal Pathogens (32). According to Kreisler (2005) the greatest reduction in the degree of tooth mobility and probing depth in the group of patients who underwent SRP + laser therapy can be mainly attributed not to the killing of bacteria in periodontal pockets, but rather to the complete removal of infected sulcular epithelium, which leads to greater attack of the connective tissue (33).…”
Section: Middle Value Pmentioning
confidence: 99%
“…Gojkov-Vukelic M. et al (2013) demonstrated a statistically significant decrease in Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis immediately and 3 months after the baseline [12]. The significant antibacterial effects against major pathogens such as Prevotella intermedia, Tannerella forsythia, Treponema denticola, and Porphyromonas gingivalis were demonstrated for Er,Cr:YSGG laser-assisted periodontal therapy in a 6-month follow-up study conducted by Gutknecht et all [13].…”
Section: Discussionmentioning
confidence: 99%
“…The use of lasers has been proposed for its bactericidal and detoxifying effect, but also for its capacity to stimulate local healing [10][11][12][13][14]. Despite the literature data showing controversial results and conclusions of various laser wavelengths used in periodontal therapy, only a few researches aimed to investigate the synergic effect promoted by the combination of different laser categories.…”
Section: Introductionmentioning
confidence: 99%
“…However, many other studies, including that of Birang et al, 27 have shown that the use of diode laser or chlorhexidine gel, as adjunctive techniques, is more effective than mechanical debridement alone in the treatment of chronic periodontitis, concluding that if routine mechanical debridement is combined with diode laser or chlorhexidine gel, it will be more effective in improving the clinical and microbiologic parameters. Gojkov-Vakelic et al 28 showed that use of diode laser beams decreased the number of active pathogens in periodontal pockets. On the other hand, the results of studies done by Moritz et al 29 and Angelov et al 30 showed that treatment with diode laser might improve periodontal pockets and periodontal parameters.…”
Section: Effectiveness Of Photodynamic Therapy In Treatment Of Peri-imentioning
confidence: 99%